Current Proplems of Culture Studies and Education - I. Y. Murzina (Образование и наука)
The paper is devoted to analyzing the specifics of culture studies, and development of this scientific sphere and relating higher school discipline in the last two decades. Given the need for integration of the humanities subjects, culture studies can provide the necessary ground for such consolidation, being aimed at the analysis and synthesis of socio-cultural conformities.The problematic field of culture studies is defined along with the modern trends of scientific research in pedagogy. In author’s opinion, the culturology analysis of educational practices should be regarded as the important direction of culture studies. The culturology approach to educational standards and academic curricula development can provide the ground for overcoming the educational and pedagogic crisis.